2013
DOI: 10.1007/s11745-013-3816-0
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Decreases C‐Reactive Protein/Albumin Ratio Improving Nutritional Prognosis and Plasma Fatty Acid Profile in Colorectal Cancer Patients

Abstract: Previous studies have shown that n-3 polyunsaturated fatty acids n-3 (n-3 PUFA) have several anticancer effects, especially attributed to their ability to modulate a variety of genomic and immune responses. In this context, this randomized, prospective, controlled clinical trial was conducted in order to check whether supplementation of 2 g/day of fish oil for 9 weeks alters the production of inflammatory markers, the plasma fatty acid profile and the nutritional status in patients with colorectal cancer (CRC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 37 publications
4
73
1
11
Order By: Relevance
“…CRP is an acute phase protein regulated by IL-6, tumor necrosis factor and other inflammatory factors (35). Therefore, CRP may indicate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an acute phase protein regulated by IL-6, tumor necrosis factor and other inflammatory factors (35). Therefore, CRP may indicate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that inflammation and nutritional status improved by intervention with fish oil administration. (7,21,22). As fish oil is rich in EPA and DHA, we therefore considered that an improved CRP and decreased serum AA/EPA ratio, or n-6/n-3 ratio could be reached by eating a diet with n-3 fatty acid, such as EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…In the Silva et al (2012) study that included only colorectal cancer patients, no change in body weight and body mass index was observed for the patients that received fish oil (P > 0.05), while both indicators decreased for the patients that did not receive fish oil (P ¼ 0.01 and P ¼ 0.03, respectively) [22]. In the Mocellin et al (2013) study, no significant changes in body weight or body mass index were observed by the end of the study period [23]. For the remaining chemotherapy studies, the duration and administration form of supplement varied.…”
Section: Body Weightmentioning
confidence: 95%
“…Moreover, these patients were compared with those that did not receive a nutritional supplement [20,22,23]. In the Bonatto et al (2012) study, the oncologic patients that received fish oil gained an average of 1.7 kg (P ¼ 0.002), while the control group lost an average of 2.5 kg [20].…”
Section: Body Weightmentioning
confidence: 99%